PROFILE OF STUDENT SELF-REGULATION LEARNING IN APPLYING TEACHING SKILLS IN ONLINE LEARNING. - Sudarman; Noor Ellyawati; Riyo Riyadi; Ratna Fitri Astuti (International Journal of Social Science, 2022)
The conceptual framework for understanding cognitive, motivational, and self-regulated learning determines the emotional aspects of the learning process. This study aims to investigate student self-regulation learning in applying teaching skills in online learning situations. The survey method is used to find out whether students really plan, organize, and help their own learning. We have asked questions according to the indicators of the Motivated Strategies for Learning Questionnaire instrument. The participants of this study were students of the Economics Education Study Program, Counseling Guidance, History, Pancasila and Civic Education, Mathematics, Indonesian Literature, and English Literature. The total participants were 116, with a composition of 25.86% male and 74.14% female. The results showed that students' self-regulation was in the medium group as many as 20 people (17.24%), the high group as many as 84 people (72.42%) and the very high group as many as 12 people (10.34%). Meanwhile, student self-regulation for each indicator achieved consists of a reherseal indicator of 31.96% in a poor group, an elaboration indicator of 57.73% in a good group, an organization indicator of 0% in a very poor group, an effort regulation indicator of 0% in a very poor group, and metacognitive indicators of 28.87% in a poor group. Based on the self-regulation group of each student and the percentage of achievement in self-regulation for each indicator, it is said that the participants already have good rehearsal and elaboration abilities, but need to improve their self-regulation skills, and independence to learn and solve problems.